MACROECONOMIC ANALYSIS AND ITS INFLUENCE ON INTERNATIONAL BUSINESS AND ECONOMIC GROWTH (Study on Indonesian country period 2008-2017) - A. Tulong, Gerard; Suhadak, Suhadak; Handayani, Siti Ragil (Profit: Jurnal Adminsitrasi Bisnis, 2018)
The research purpose is to empiricaly analyze the influence and importance of Macroeconomic on International Business and Economic Growth in Indonesia period 2008-2017. Interest Rates, Exchange Rates and Inflation Rates are Macroeconomic Indicators. Foreign Direct Investment, Expot and Import activity are International Business Indicators. Gross Domestic Product, Private and Government Consumptions are Economic Growth Indicators. This explanatory research will use quantitative research approach. Population & Sample are time series data period 2008-2017, all data are secondary data taken from credible institutions as Bank Indonesia, Statistics Indonesia, Burreau of Investment Indonesia, Indonesia National Single Window and World Bank. The data analyzed using GeSca operating system online and signed reflective. The descriptive analysis shown Indonesiaâ€™s Macroeconomic volatile, International Business Activity and Economic Growth. The research results shown that there are one variable has insignificant effect and two variables has significant effect. Macroeconomic has insignificant effect on International Business, Macroeconomic has negative-significant effect to Economic Growth and International Business has positive-significant to Economic Growth.Â